ANATOMI KONSEP PENYELESAIAN KONFLIK AGRARIA: STUDI PERBANDINGAN ANTARA RANAH KEBIJAKAN DAN RANAH PERJUANGAN AGRARIA - Antoro, Kus Sri (BHUMI: Jurnal Agraria dan Pertanahan, 2018)
This article is a conceptual idea of the comparison between a research finding and reality in the community related to the agrarian conflict resolution. The study is entitled Resolution Policy on Contemporary Agrarian Conflict, which is one of the systematic studies carried out by STPN in 2012; while the aforementioned reality in the society is gathered from records of the dynamics of agrarian conflict and struggle in several areas collected by Forum Komunikasi Masyarakat Agraris (FKMA), which are published by FKMA and other official media. By exploring and comparing the conceptual ideas of the two written sources, this article is intended to map out the approaches and models of agrarian conflict resolution, especially according to the perceptions and interests of the three actors of agrarian political economy, namely the state, market and society. Keywords: agrarian resources, conflict, conflict resolution